2016
DOI: 10.21037/jtd.2016.08.69
|View full text |Cite
|
Sign up to set email alerts
|

Asian perspective in surgery: thoracic surgery in Turkey

Abstract: Turkey with a population of 78 million is located between Asia and Europe geographically and culturally. There are 577 active pure thoracic surgeon and 37 thoracic surgery teaching units. Thoracic surgeons usually deal with lung cancer patients due to relatively higher rate of tobacco usage as well as inflammatory diseases such as pulmonary hydatid disease, bronchiectasis and empyema. Minimally invasive thoracic surgery has been a new approach which is being adapted by increasingly more surgeons. There are a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…[ 2 ] The first VATS lobectomy in Türkiye was performed in 2001, and its use has since been increasing, particularly in the field of lung cancer surgery. [ 9 ] Although VATS is an increasing field of application in bronchiectasis, one of the infectious diseases of the lung, the presence of enlarged and adherent lymph nodes, bleeding during dissection, presence of fragile tissue, existing adhesions, enlarged bronchial arteries, and vascular structures are significant obstacles to this application. However, our literature review revealed that there are few studies on this subject.…”
Section: Discussionmentioning
confidence: 99%
“…[ 2 ] The first VATS lobectomy in Türkiye was performed in 2001, and its use has since been increasing, particularly in the field of lung cancer surgery. [ 9 ] Although VATS is an increasing field of application in bronchiectasis, one of the infectious diseases of the lung, the presence of enlarged and adherent lymph nodes, bleeding during dissection, presence of fragile tissue, existing adhesions, enlarged bronchial arteries, and vascular structures are significant obstacles to this application. However, our literature review revealed that there are few studies on this subject.…”
Section: Discussionmentioning
confidence: 99%
“…Since state hospitals are the institutions where all citizens can receive health care services without distinction of social security institutions, open heart surgery and angiography make these hospitals more advantageous for patients. According to recent data, cardiac surgery and angiography services are provided in 207 centers in 46 provinces in Turkey 20 . One hundred twentytwo of these centers are private hospitals, 44 are university hospitals, and 40 are state hospitals 21 .…”
Section: Discussionmentioning
confidence: 99%